Transfer Pricing Pada Perusahaan Multinasional: Pengaruh dari Pajak, Tunneling Incentive, dan Mekanisme Bonus - Margareta Ruly Anggarsari (Pascasarjana Universitas Sultan Ageng Tirtayas, 2023)
This study aims to empirically test: 1) The Effect of Taxes, 2) Tunneling Incentives, and 3) Bonus Mechanisms on Transfer Pricing. This study consists of 3 (three) independent variables, namely Tax (X1), Tunneling Incentive (X2), and Bonus Mechanism (X3) with 1 (one) dependent variable, namely Transfer Pricing (Y). This study uses a quantitative research type and the data source in this study is secondary data obtained from www.idx.co.id, with the selected sample being Multinational Mining Sub-Industry Companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021, with a total sample of 11 companies. The sampling technique used was non-probability sampling and purposive sampling, and the data analysis techniques used in this study included descriptive statistical tests, classical assumption tests, hypothesis testing and multiple linear regression tests with the help of the SPSS v.25 application. The results showed that the Tax variable has no effect on the Transfer Pricing decision, the Tunneling Incentive variable has effect on the Transfer Pricing decision, and the Bonus Mechanism has effect on the Transfer Pricing decision.